Spatial distribution, host specificity and genetic diversity of Onchobothrium antarcticum in the Southern Ocean - Gordeev, Ilya I.; Polyakova, Tatyana A.; Volkov, Alexander A. (Polish Polar Research, 2021)
In this work we summarize the current knowledge on the spatial distribution, host specificity and genetic diversity of Onchobothrium antarcticum, an endemic Antarctic cestode. We recorded it in seven fish species, elasmobranchs Amblyraja georgiana, Bathyraja eatonii, and B. maccaini and teleosts Antimora rostrata, Chionobathyscus dewitti, Dissostichus mawsoni, and Muraenolepis marmorata, caught in the Ross Sea, the D’Urville Sea, the Mawson Sea, and the Weddell Sea. The infection of A. rostrata from the part of its distribution to the south of the Falkland Islands is reported for the first time. We obtained partial 28S rDNA and cox1 sequences of plerocercoids and adults of O. antarcticum and analyzed them together with a few previously published sequences. Based on the results of the phylogenetic analysis, we cannot rule out that O. antarcticum is in fact a complex of cryptic species.